Constantine’s decennalia and his fourth consulship on a follis from Lugdunum - Bontas, Andrei (KOINON: The International Journal of Classical Numismatic Studies, 2020)
In 2015, a French auction house offered a reduced follis/nummus of Constantine I, minted at Lugdunum (Lyon), in celebration of the emperor’s double occasion: his decennalia and his fourth consulship. These specific issues are very rare, and any new recorded specimen is a noteworthy addition to a corpus of rare and historically significant coins.